دور الخبرة في دراسة السوق العقارية - بن ناصر, فتحي (University of Eloued جامعة الوادي, 2023)
التقييم العقاري هو عملية فنية تعتمد على تقنيات وبديهيات ومعايير مضبوطة بهدف الوصول لما هو مطلوب وذلك بتحديد قيمة تجارية أو إيجاريه لعقار ما , ويهدف القيام بما هو مطلوب للوصول للنتائج المرجوة , وتهدف عملية التقييم على ضمان الحقوق والمحافظة على الملكيات , وعلى منفذي عمليات التقييم لتحديد القيمة الحقيقية للعقار لابد من الجمع بين الكفاءة والن ا زهة والإلمام بالقد ا رت المهنية من جهة , ومن جهة ثانية العمل على احت ا رم المبادئ والأهداف لتحقيق الوصول لنتائج حقيقية. وفي إطار انتهاج الدولة سياسة الانفتاح والاعتماد على السوق العقارية الحرة في ظل النظام ال أ رسمالي, بادر المشرع في سن قوانين وتشريعات لمواكبة متطلبات المرحلة , والاعتماد على د ا رسة السوق الحرة كمرجعية لتحديد الأسعار .Real estate appraisal is a technical process that relies on exact techniques, axioms, and standards in order to reach what is required by determining a commercial or rental value for a property. It aims to do what is required to reach the desired results. The appraisal process aims to guarantee rights and preserve property. Real estate must combine competence, integrity and familiarity with professional capabilities on the one hand, and on the other hand work to respect the principles and objectives to achieve real results. Within the framework of the state's policy of openness and reliance on the free real estate market under the capitalist system, the legislator took the initiative to enact laws and legislation to keep pace with the requirements of the stage, and to rely on the study of the free market as a reference for setting prices.
مذكرة ماستر
Keywords: التقييم العقاري, الخبرة العقارية, طرق التقييم , د ا رسة السوق العقارية; real estate appraisal, real estate experience, evaluation methods, real estate market study